2020
DOI: 10.1098/rspb.2019.2968
|View full text |Cite
|
Sign up to set email alerts
|

Ancient mitogenomes show plateau populations from last 5200 years partially contributed to present-day Tibetans

Abstract: The clarification of the genetic origins of present-day Tibetans requires an understanding of their past relationships with the ancient populations of the Tibetan Plateau. Here we successfully sequenced 67 complete mitochondrial DNA genomes of 5200 to 300-year-old humans from the plateau. Apart from identifying two ancient plateau lineages (haplogroups D4j1b and M9a1a1c1b1a) that suggest some ancestors of Tibetans came from low-altitude areas 4750 to 2775 years ago and that some were involved in an expansion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Besides, we also identified a close genetic relationship between modern Sherpa/Tibetan and ancient Qijia people from the upper Yellow River basin (Lajia and Jinchankou), suggesting Qijia people as the representative of Neolithic millet farmers played an important role in the formation of modern Tibetans although they shared more alleles with Neolithic Yangshao, Longshan people from Central Plain in Henan Province, and Houli people from Shandong Province. Our autosome-based genetic links between ancient populations from northeast TP were consistent with recent archeological, Y-chromosomal, and mitochondrial evidence for the colonization and peopling of the Qinghai-Tibet Plateau ( Chen et al, 2015 ; Wang et al, 2018a ; Zhang et al, 2018 ; Li et al, 2019b ; Ding et al, 2020 ). Archeologically attested charred grains and the corresponding carbonization dating data provided by Chen et al suggested that a novel agropastoral economy facilitated Neolithic millet farmers to enjoy year-round living and to successfully occupy the northeastern TP around 3,600 years ago ( Chen et al, 2015 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Besides, we also identified a close genetic relationship between modern Sherpa/Tibetan and ancient Qijia people from the upper Yellow River basin (Lajia and Jinchankou), suggesting Qijia people as the representative of Neolithic millet farmers played an important role in the formation of modern Tibetans although they shared more alleles with Neolithic Yangshao, Longshan people from Central Plain in Henan Province, and Houli people from Shandong Province. Our autosome-based genetic links between ancient populations from northeast TP were consistent with recent archeological, Y-chromosomal, and mitochondrial evidence for the colonization and peopling of the Qinghai-Tibet Plateau ( Chen et al, 2015 ; Wang et al, 2018a ; Zhang et al, 2018 ; Li et al, 2019b ; Ding et al, 2020 ). Archeologically attested charred grains and the corresponding carbonization dating data provided by Chen et al suggested that a novel agropastoral economy facilitated Neolithic millet farmers to enjoy year-round living and to successfully occupy the northeastern TP around 3,600 years ago ( Chen et al, 2015 ).…”
Section: Discussionsupporting
confidence: 84%
“…Mitochondrial DNA (mtDNA) variations of modern Tibetan also provided clues that the upper Yellow River millet farmers first adopted cold-tolerant barley agriculture and then permanently inhibited it in the TP ( Li et al, 2019b ). Ancient mitogenomes of 5,200- to 300-year-old humans from Tibet, Gansu, Qinghai and Sichuan provinces also revealed that the D4j1b-represented ancestral population expanded from the low-altitude area to the core region of the TP around 4,750 to 2,775 years ago ( Ding et al, 2020 ). Uniparental genetic evidence from Y-chromosome phylogeny also showed that the Yellow River farmers with the paternal founding lineage of O α 1c1b-CTS5308 dispersed to the TP had triggered the formation and expansion of modern high-altitude Tibeto-Burman speakers ( Wang et al, 2018a ).…”
Section: Discussionmentioning
confidence: 99%
“…S5). E_BA and E_LBA harbor high proportions of the haplogroup D (~36.70 and 32.00%, respectively), which is a common lineage in ancient and present-day NEA populations ( 42 , 43 ) including northern Chinese (18.20 to 44.80%) and ancient Mongolians (31.20%) ( Figs. 1A and 3E and table S3).…”
Section: Resultsmentioning
confidence: 99%
“…S5). E_BA and E_LBA harbor high proportions of the haplogroup D (~36.70 and 32.00%, respectively), which is a common lineage in ancient and present-day NEA populations (42,43) S3). E_LBA also shows nonsignificant genetic distances to some of these NEA populations, specifically two ancient Gan-Qing populations (GQQijia_BA and GQKayue_LBA; F ST < 0.05, P > 0.05) and four present-day populations (Japanese, Mongolian, Tu, and Oroqen; F ST < 0.03, P > 0.05) (fig.…”
Section: Genetic Origins and Complexity Of Ba Xinjiang Populationsmentioning
confidence: 99%
“…Haplogroup J1-M267 coalescence time estimates were computed with normally distributed age prior of 18,741 ± 1874 years for the node in our phylogeny resembling the whole haplogroup J1-M267 MRCA published previously 15 . We chose the calibration method with a node age, to avoid introducing bias due to reported substantial Y chromosome mutation rate variation among different haplogroups 39 , 40 , 83 , 84 . We used no other topology constraint in our analyses.…”
Section: Methodsmentioning
confidence: 99%